Pelatihan Pembuatan Sabun Cuci Piring dari Minyak Jelantah Sebagai Upaya Pemanfaatan Limbah UMKM Tahu Walik Pasca Pandemi Covid-19 - Yayan Adi Saputro; Nurul Fadillah; Nor Khanifah (Edumedia Solution, 2022)
Cooking oil is oil derived from purified plant or animal fats—liquid forms at room temperature and usually frying food. Cooking oil is produced from palm oil on a large scale; the filtering process is carried out twice. This causes the content of unsaturated fatty acids and makes the cooking oil quickly damaged in the frying process because, in the frying process, the oil will be heated continuously at a high temperature. The oil will be directly mixed with the outside air during the frying process, resulting in an oxidation reaction. This is what is known as cooking oil, which is cooking oil that has been used for frying. Due to the large amount of waste cooking oil produced, it is necessary to recycle used cooking oil, one of which is soap's essential ingredient. We students of Unisnu KKN class XI group 76 will conduct training on soap making with used cooking oil as the base material produced by Tahu Walik Bu Ida's partner, which will be carried out at the partner's house RT 08/ RW 03 Ujung Batu, Jepara. By utilizing waste cooking oil processed into soap, it is hoped that partners will be aware that used cooking oil can be utilized.